DISTRIBUTION AND ANTIBIOTICS SUSCEPTIBILITY PATTERNS OF ENTEROCOCCUS SPP. FROM A SELECTED HOSPITAL IN INDIA - Getso, Muhammad I.; Sundaramoorthy, Subha; Kanishka, H. D.; Aliyu, Mansur; Yusuf, Ibrahim; Azeez-Akande, O.; Daneji, Isah M.; Sharif, Alhassan A. (FUDMA JOURNAL OF SCIENCES, 2020)
Enterococci cause recurrent infections, especially among hospitalized patients. Their potential for resistance to multiple antibiotics and incumbent treatment failure constitutes a significant cause of morbidity and mortality. In this study, we aimed to determine the distribution of Enterococcus species from clinical samples and their antibiotic resistance profiles to supporting patients’ treatments based on informed-decision. We conducted a cross-sectional study at SRM Medical College Hospital, Tamil Nadu, India, from January to December 2014. Sixty Enterococcus isolates, from different clinical samples, were included in the study. The isolates were identified to species level based on sugar fermentation and biochemical reactions. The antibiotic susceptibility profile was determined using disk diffusion and agar dilution methods based on CLSI guidelines. The majority of Enterococcus isolates were recovered from urine samples (51.67%) and pus (38.33%). The predominant isolates were E. fecalis (55%) and E. fecium (33.30 %,). Others were E. avium (3.3%) and 1.7 % each for E. durans and E. raffinosus. Overall, the isolates demonstrated the highest frequency of resistance to high-level gentamicin (33.30%), and one-third (33.30%) of the isolates were multidrug-resistant. Because the majority of the drug-resistant isolates were from urine and pus samples, we concluded that suspected cases of UTIs, wound infections, and sepsis need critical evaluation for possible enterococcal infection. Clinical use of gentamicin, among other antibiotics, shall be closely monitored while treating infections.